Therapeutic efficacy of repeated cycles of local IL-2 injections in mice carrying slowly growing tumour grafts - Símová, J; Bubeník, J; Indrová, M; Bubeníková, D; Jandlová, T (Folia biologica, 1993)
Local IL-2 administration prior to transplantation of murine sarcoma virus (MSV Harvey)-induced tumour MSVT2 provided a model of slowly growing tumours suitable for long-term investigation of the therapeutic efficacy of repeated IL-2 injection cycles. Challenge of mice with the dose of sarcoma cells, which was lethal for 20/20 untreated control recipients, revealed that 8/20 IL-2-pretreated mice were protected by the local IL-2 treatment and survival indefinitely. Nine out of twenty IL-2-pretreated mice died during the same time period as the control mice, i.e., during 36 days, and 3/20 IL-2 pretreated mice were tumour-negative until day 60, when incipient tumours arose. The three late tumours were used as a model to investigate the therapeutic efficacy of the new cycles of repeated local IL-2 administration. It was found that no resistance to IL-2 immunotherapy was induced by pretreatment of the late tumours and that the tumours were repeatedly susceptible to local IL-2 treatment. Spleen cells of the tumour-bearing mice, which were not cytotoxic for MSVT2 tumour cells in vitro, could be made cytotoxic by addition of exogenous IL-2.
Keywords: Cytotoxicity, Immunologic; Moloney murine sarcoma virus; Retroviridae Infections; Moloneyho virus myšího sarkomu; retrovirové infekce; Tumor Virus Infections; buňky K aktivované lymfokiny; interleukin-2; Drug Administration Schedule; Antineoplastic Agents; injekce subkutánní; zvířata; experimentální sarkom; myši; Injections, Subcutaneous; Interleukin-2; Mice; Killer Cells, Lymphokine-Activated; Male; Neoplasm Transplantation; transplantace nádorů; Spleen; cytotoxicita imunologická; protinádorové látky; Mice, Inbred Strains; Animals; mužské pohlaví; inbrední kmeny myší; Sarcoma, Experimental; rozvrh dávkování léků; slezina; infekce onkogenními viry